Peningkatan Hasil Belajar Sub Tema Indahnya Persatuan dan Kesatuan Negeriku melalui Strategi Giving Question And Getting Answer Dikombinasikan Dengan Media Puzzle - Pujianto, Pujianto (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
The value of learning outcomes in thematic learning in class IV of SD Negeri Bandarharjo 01 Semarang City based on the results of several student daily tests is still lacking. The results of this study can be seen from the results of the average score of each student on four daily tests, namely 59.8, where the average student lacks the sub-theme of the beauty of the unity and integrity of my country, the method used in the learning material is not appropriate for the use of inappropriate media or even not using the media at all, teacher motivation towards student learning is still lacking, and traditional learning also makes the value of learning completeness so far still far from ideal. Learning media with puzzle media carried out in thematic learning sub-theme of the beauty of the unity and integrity of my country in class IV SD Negeri Bandarharjo 01 Semarang City is very helpful in increasing understanding, presenting data in an interesting and reliable manner, making it easier to interpret data and obtain the necessary information. This study is intended to answer the problem, namely whether the strategy of giving questions and getting answers combined with puzzle media can improve learning outcomes for the sub-theme